First Report of Recurrent Intramuscular Lipoma after Decompression Surgery of the Lumbar Spine - Klessinger, Stephan; Freund, Wolfgang; Karpel-Massler, Georg; Wirtz, Christian; Thal, Dietmar; Halatsch, Marc-Eric (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Intramuscular or infiltrating lipomas are rare. We present a 58-year-old man with an intramuscular lipoma developing after decompression surgery for lumbar spinal canal stenosis. One year after macroscopically complete lipoma resection, an even bigger recurrent tumor had to be removed. The lumbar paraspinal musculature is a very uncommon site for an intramuscular lipoma. A relation between surgery and the growth and recurrence of an intramuscular lipoma has not been described previously in the literature.
Keywords: lipoma; spine surgery; spinal canal stenosis